Barley research in India: Retrospect & prospects - Kumar, Vishnu Kumar; Khippal, Anil Khippal; Singh, Jogendra Singh; R, Selvakumar; Malik, Rekha; Kumar, Dinesh; Kharub, Ajit Singh; Verma, Ramesh Pal Singh; Sharma, Indu (Journal of Cereal Research, 2014)
Barley is one of the founder crops of old world agriculture and wasone of the first domesticated cereals. It is fourth largest cereal cropafter maize, wheat and rice in the world with a share of 7 per cent ofthe global cereal production. The crop is considered as poor manâ€™scrop and better adaptable to problematic soils and marginal lands.It is not only useful for malting, feed and food purposes but also itsÎ²-glucans is helpful in lowering the risk of cardio-vascular diseases.Prior to the inception of AICRP on Barley, pure line selections inthe indigenous land races were employed, which resulted in thedevelopment of several barley varieties like NP 13, NP 21 (New Pusa),C 251, K 12, K 18, K 24 (Kanpur, UP), BR 22 & BR 32 (Sabour, Bihar),T4, T5, C 138 and C 164 (United Punjab). The All India CoordinatedBarley Improvement Project (AICBIP), involving ICAR and SAUcenters was initiated in 1966-67 to do the collaborative research.During the IXth five year plan, both barley and wheat coordinatedprojects were merged and combined programme was named as â€œAllIndia Coordinated Wheat and Barley Improvement Projectâ€ in 1997and this arrangement is being continued since then. Keeping in mindthe priorities as abiotic, biotic stress, dual, malt and food purposes, atotal of 122 barley varieties and 15 genetic stocks, agrotechnologiesand disease and pest management strategies have been developedfrom the barley improvement programme and are described in thisreview article.